Pemertahanan Bahasa Jawa dalam Komunikasi Anggota Organisasi Ikatan Mahasiswa Bidikmisi Universitas Trunojoyo Madura (Kajian Sosiolinguistik) - Beny Mawarsih, Putri; Febriani, Ika (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
This study aims to determine the maintenance of Javanese language by speakers in organization of the Bidikmisi Student Association at Trunojoyo Madura University. Language preservation is one of the studies in the sociolinguistic. Sociolinguistic combine two fields of science, namely sociology which studied social life and linguistics studied about language. The research method used was a descriptive qualitative method because the data studied in the form of words, not variables. The data collection technique used were recording, interview, observation, and documentation. The data analysis technique used was taxonomic analysis. The data sources analyzed were Javanese’s speaker. The results of the study showed that language maintenance in the Bidikmisi Student Association at Trunojoyo Madura University still being pursued. The defense of the Javanese language evidenced by the presence of conversations used Javanese language on formal or informal situations between members of the organization. There are three factors which can cause a language friction. There are defense strategies that can be attempted to conserve the language.